Redução dos desperdícios e perdas no setor de embalagem de motores elétricos industriais - Melo, José Aparecido de (2017)
This work was developed based on theoretical basis, aiming at the implementation of WCM (World Class Manufacturing) methodology in the model center (packaging sector) that is composed of three lines of boxing of electric motors. The work was developed in three parts, first it was necessary to carry out a study on the topic addressed, then the implementation of the WCM methodology and, finally, analysis of the results obtained in the implementation of the methodology in a model center. The objectives of the cost reduction work using the WCM methodology, raised in code deployment were achieved. With the improvements implemented in the boxing lines (model center) there was a reduction in losses due to product inspection, due to lack of programming and product inspection. With the reduction of labor there was an increase of 11% in productivity in the model center in a daily production of 2.100 motors..